PELATIHAN INOVASI PRODUK PENGOLAHAN HASIL LAHAN PEKARANGAN DAN LIMBAH ORGANIK DI KWT MAWAR BPP MARITENGGAE - Yaya, Astrina Nur Inayah; Nurwidah, Andi; Salfiana, Salfiana; Hasanuddin, Fenny; Muhanniah, Muhanniah; Thamrin, Nining Triani; Mursalat, Aksal; AR, Trisnawaty; Yusrianti, Yusrianti; Reskianti, Reskianti; Zahilah, Rizka Nur; Alus, Yuliana Jurita; Safri, Eka Pratiwi (Jurnal Pengabdian Masyarakat Sabangka, 2025)
The Mawar Women Farmers Group (KWT) at BPP Maritenggae faces challenges in optimizing land yard products and organic waste utilization, as agricultural production increases, organic waste such as crop residues, fruit peels, and other organic materials are often not well utilized properly resulting in untapped economic potential. This community service program aims to enhance KWT members' skills in processing land products and organic waste into innovative, marketable products. The training employs lectures, demonstrations, and hands-on practice, providing participants with real experience in production, packaging, and marketing. The results indicate an increase in participants' knowledge and skills in processing organic waste into compost and transforming agricultural products into value-added goods. Furthermore, this training fosters an entrepreneurial spirit among KWT members, potentially improving their economic well-being and self-sufficiency.